2012
DOI: 10.4100/jhse.2012.74.05
|View full text |Cite
|
Sign up to set email alerts
|

The effects of glutamine supplementation on performance and hormonal responses in non-athlete male students during eight week resistance training

Abstract: Hakimi M, Mohamadi MA, Ghaderi Z. The effects of glutamine supplementation on performance and hormonal responses in non-athlete male students during eight week resistance training. J. Hum. Sport Exerc. Vol. 7, No. 4, pp.770-782, 2012. The aim of this study was to determine the effects of glutamine supplementation on performance, and hormonal changes during an 8-week resistance training program in non athlete male students. Thirty healthy non athlete male (age 21.25 ± 1.6 years, height 173.2 ± 3.2 cm, body mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Oral supplementation of glutamine (0.35g/kg/day) by 15 non-athlete male students for 8 weeks, caused significantly greater increases in upper and lower body strength, explosive muscular power, blood testosterone, GH and IGF-1 when compared to the placebo group. Furthermore, in the study group there was improved body composition (increased body mass, fat-free mass and reduced body fat) and vertical jump (62.31 ± 5.22 pre-and 67.11 ± 4.44 post-supplementation) [79]. Glutamine supplementation plays a key role in recovery after muscle injury.…”
Section: L-glutaminementioning
confidence: 86%
See 1 more Smart Citation
“…Oral supplementation of glutamine (0.35g/kg/day) by 15 non-athlete male students for 8 weeks, caused significantly greater increases in upper and lower body strength, explosive muscular power, blood testosterone, GH and IGF-1 when compared to the placebo group. Furthermore, in the study group there was improved body composition (increased body mass, fat-free mass and reduced body fat) and vertical jump (62.31 ± 5.22 pre-and 67.11 ± 4.44 post-supplementation) [79]. Glutamine supplementation plays a key role in recovery after muscle injury.…”
Section: L-glutaminementioning
confidence: 86%
“…A lot of research concerning on oral supplementation with Gln and its effect on physical performance, took place in Iran [1,78,79]. Research conducted by Dabidi Roshan focused on immunological aspect.…”
Section: L-glutaminementioning
confidence: 99%
“…The independent sample t-test in table II showed that glutamine administration affects the vertical jump results 48 hours after hitting the jumping smash. In their research, Hakimi et al (2012) stated that the vertical jump results were better in the group given glutamine than placebo [22].…”
Section: Discussionmentioning
confidence: 99%
“…The GLA-GLN relationship also plays a vital role in muscular metabolism, as GLN is stored and released predominantly by the skeletal muscle [18]. Also, it is the most abundant non-essential amino acid in human muscle [19]. The skeletal muscle amino acid metabolism generates GLN to detoxify the ammonia produced at this level [18].…”
Section: Positive and Negative Aspects Of The Biological Behaviour Of...mentioning
confidence: 99%
“…Because of its immunomodulatory role, GLN is widely used in sports nutrition as a food supplement [20]. An experimental study concluded that GLN supplementation increases muscular power and strength and enhances performance during resistance training [19]. Also, sports recovery acceleration and muscular fatigue reduction are essential for sports performance.…”
Section: Positive and Negative Aspects Of The Biological Behaviour Of...mentioning
confidence: 99%